Changing Patterns of Drug Abuse and Criminality Among Crack Cocaine Users in New York City, 1988-1989 - Fagan, Jeffrey ([Verlag nicht ermittelbar], 1992)
This collection examines the characteristics of users and sellers of crack cocaine and the impact of users and sellers on the criminal justice system and on drug treatment and community programs. Information was also collected concerning users of drugs other than crack cocaine and the attributes of those users. Topics covered include initiation into substance use and sales, expenses for drug use, involvement with crime, sources of income, and primary substance of abuse. Demographic information includes subject's race, educational level, living area, social setting, employment status, occupation, marital status, number of children, place of birth, and date of birth. Information was also collected about the subject's parents: education level, occupation, and place of birth.